2004
DOI: 10.1002/pbc.20210
|View full text |Cite
|
Sign up to set email alerts
|

Poor response to desmopressin acetate (DDAVP) in children with Hermansky-Pudlak syndrome

Abstract: DDAVP seldom improves the BT of Puerto Rican children with HPS. Response to DDAVP should be determined individually and platelet transfusion should remain the treatment of choice for a major bleeding episode or surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Desmopressin, a synthetic vasopressin, has been used with variable success for prophylaxis of minor bleeding in patients with HPS. [23][24][25] If major bleeding is anticipated, a platelet transfusion should be considered. In any event, it is reasonable to have platelets available in case excessive bleeding occurs during or after surgery.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Desmopressin, a synthetic vasopressin, has been used with variable success for prophylaxis of minor bleeding in patients with HPS. [23][24][25] If major bleeding is anticipated, a platelet transfusion should be considered. In any event, it is reasonable to have platelets available in case excessive bleeding occurs during or after surgery.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Some degree of mucocutaneous hemorrhage has been reported in practically all HPS patients [54]. Notably, an estimated 40% of HPS patients are vulnerable to life-threatening hemorrhage with an approximate 10% supposedly succumbing to bleeding complications [55,56,57].…”
Section: Elements Of Hpsmentioning
confidence: 99%
“…Another study, employing molecular characterization, showed that 15 of 19 Puerto Rican children with HPS1 gene mutation (present in >50% of Puerto Ricans with HPS) and 2 of 4 without HPS1 gene mutation failed to improve their bleeding times after test doses of DDAVP. Previous bleeding studies in Dutch and Belgian patients have been criticized for failing to identify mutation types, highlighting the complexity of determining effectual treatment [54, 73]. …”
Section: Treatmentmentioning
confidence: 99%
“…PCFT-SLC46A1, OCA1, HPS , and HIV serotypes), and that also included healthy subjects, have been conducted in Puerto Ricans within the island [49–52]. Reports of the frequencies of genetic biomarkers and phenotyping of drug metabolism or valid biomarkers in the Puerto Rican population are necessary to support efforts towards the adoption of a personalized medicine paradigm in the island.…”
Section: Discussionmentioning
confidence: 99%